Gradual Thickening of the Peritubular Lamina Propria in Healthy Boar Seminiferous Tubules Due to Cryptorchidism: Increased Immunoexpression of Diverse Proteins in Sertoli and Myoid Cells - Vicente Seco-Rovira; Jesús Martínez-Hernández; Laís Freire-Brito; Ester Beltrán-Frutos; Juan Francisco Madrid; Luis Miguel Pastor (Animals)
In testicular pathology, the accumulation of extracellular matrix and thickening of the peritubular lamina propria are associated with altered spermatogenesis. This study evaluated the immunoexpression of certain proteins in Sertoli and myoid cells of cryptorchid boar seminiferous tubule sections to determine the role of these cells in peritubular lamina propria thickening. Sections of normal seminiferous tubules and those with varying degrees of atrophy (I–III) were studied using histochemical and immunohistochemical techniques. A semiquantitative analysis of histochemical staining or immunostaining intensity in these sections was performed. Gradual thickening of the peritubular lamina propria was observed between stage II and III sections. HSP47 was present in myoid and Sertoli cells in normal sections and was significantly increased in stage II and III sections. The increase in stage II was dependent on Sertoli cells, while in stage III, it depended on myoid cells. The vimentin increases in stage I sections were due to Sertoli cells and later to myoid cells in stages II and III. α-actin and collagen IV immunoreactivity were observed from the early stage of atrophy, with a significant increase in stage III. In conclusion, in porcine spontaneous cryptorchidism, the seminiferous tubule exhibits gradual fibrotic alterations in the peritubular lamina propria, initially related to changes in the Sertoli cell phenotype and later, in the final stages, to myoid cells. Collagen I deposition appears to be caused by myoid cells, initiating the sclerosis of the seminiferous tubules.